Analysis of cantilever steel beam - Siti Nurul Huda, Mohd Sharif (2018)
The usage of steel beam has been run for a long time in a construction industry. The application of cantilever steel beam become popular choice of Industry, by extending the steelwork design into residential housing. The objectives of this project are to analyse the forces and stresses in a selective size steel cantilever beam and finding the maximum vertical force (Newton) for beam which is hot rolled shape IPE 120 and is made of Fe430 steel. The thesis presents the linear analysis of cantilever steel beam by using ANSYS 12.0, Finite Element Software was use to model the cantilever steel beam with I beam section IPE 120. ANSYS software is used to analyse linear static of the forces and stress for the elastic 2D cantilever steel beam. The model geometry is defined with elements and nodes. This thesis also shows the theoretical calculation of stress. The results from ANSYS software were compared with the theoretical calculation results. The finite element behaviour of cantilever steel beam was found to be slightly different with the theoretical calculation and behaviour.